A novel P53/POMC/Gαs/SASH1 autoregulatory feedback loop activates mutated SASH1 to cause pathologic hyperpigmentation. Issue 4 (25th November 2016) - Zhou, Ding'an; Wei, Zhiyun; Kuang, Zhongshu; Luo, Huangchao; Ma, Jiangshu; Zeng, Xing; Wang, Ke; Liu, Beizhong; Gong, Fang; Wang, Jing; Lei, Shanchuan; Wang, Dongsheng; et al.
Abstract: p53‐Transcriptional‐regulated proteins interact with a large number of other signal transduction pathways in the cell, and a number of positive and negative autoregulatory feedback loops act upon the p53 response. P53 directly controls the POMC/α‐MSH productions induced by ultraviolet (UV) and is associated with UV‐independent pathological pigmentation. When identifying the causative gene of dyschromatosis universalis hereditaria (DUH), we found three mutations encoding amino acid substitutions in the gene SAM and SH3 domain containing 1 (SASH1), and SASH1 was associated with guanine nucleotide‐binding protein subunit‐alpha isoforms short (Gαs). However, the pathological gene and pathological mechanism of DUH remain unknown for about 90 years. We demonstrate that SASH1 is physiologically induced by p53 upon UV stimulation and SASH and p53 is reciprocally induced at physiological and pathophysiological conditions. SASH1 is regulated by a novel p53/POMC/α‐MSH/Gαs/SASH1 cascade to mediate melanogenesis. A novel p53/POMC/Gαs/SASH1 autoregulatory positive feedback loop is regulated by SASH1 mutations to induce pathological hyperpigmentation phenotype. Our study demonstrates that a novel p53/POMC/Gαs/SASH1 autoregulatory positive feedback loop is regulated by SASH1 mutations to induce pathological hyperpigmentation phenotype.